A novel gait for toddler biped and its control using PIC 16F877A - Akhtaruzzaman, Md.; Shafie, Amir Akramin (2011)
Beside the humanoid platform both in the male and female form, a huge numbers of researches are advancing to design and develop the humanoid robot kits ensuring the educational, research and business value. Because of the smart design with few numbers of actuators, smaller in size and weight, lower power having simplified controller and modest price make the humanoid robot kits more attractive, charismatic and representable to the general public. In this paper the small sized biped robot called TODDLER is delineated intricately. The paper also exemplifies the design strategies of a novel walking gait for this robot kit. A new control architecture is also proposed and designed based on PIC 16F877A which makes the biped system more valuable for educational activities on robotics research especially for humanoid robots. A rudimentary algorithm, that helps the biped kit to perform its gait to navigate, is represented and its simulated results are also scrutinized in this paper.